2014
DOI: 10.1094/pdis-05-13-0530-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Botryosphaeria dothidea, Diplodia seriata, and Neofusicoccum luteum Associated with Canker and Dieback of Grapevines in Tunisia

Abstract: In 2011, common symptoms of grapevine dieback were frequently observed in 2- to 5-year-old table grape (Vitis vinifera L.) cvs. in four vineyards located in northern Tunisia. The symptoms included dead spur and cordons, shoot dieback, and sunken necrotic bark lesions, which progressed into the trunk resulting in the death of large sections of the vine. Longitudinal and transversal sections of cordons and spurs from symptomatic vines revealed brown wedge-shaped cankers of hard consistency. Twelve symptomatic sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“… Ascomycota Cladosporiaceae E, P, S ■; ▲; ● 0.5; 9.1; 0.2 [ 28 , 88 ] Cladosporium sphaerospermum Ascomycota Cladosporiaceae P, S 1.1 [ 88 ] Cryptococcus sp. Basidiomycota Cryptococcaceae E, S ■; ▲; ● 0.3; 2.8; 0.2 [ 28 , 92 ] Diplodia seriata Ascomycota Botryosphaeriaceae E, P, S ■; ▲ 0.2; 0.3 [ 78 , 79 , 82 , 88 , 91 , 92 , 94 , 97 , 98 , 102 , 104 , 108 , 123 , 124 , 125 , 126 , 127 , ...…”
Section: Figure A1mentioning
confidence: 99%
“… Ascomycota Cladosporiaceae E, P, S ■; ▲; ● 0.5; 9.1; 0.2 [ 28 , 88 ] Cladosporium sphaerospermum Ascomycota Cladosporiaceae P, S 1.1 [ 88 ] Cryptococcus sp. Basidiomycota Cryptococcaceae E, S ■; ▲; ● 0.3; 2.8; 0.2 [ 28 , 92 ] Diplodia seriata Ascomycota Botryosphaeriaceae E, P, S ■; ▲ 0.2; 0.3 [ 78 , 79 , 82 , 88 , 91 , 92 , 94 , 97 , 98 , 102 , 104 , 108 , 123 , 124 , 125 , 126 , 127 , ...…”
Section: Figure A1mentioning
confidence: 99%
“…However, due to the ban of sodium arsenate, several vine dieback cases have been reported, often with unidentified causes. However, recent studies conducted on vineyards showing declining grapevines reported the occurrence of three Botryosphaeriaceae species to be associated with grapevine dieback in Tunisian vineyards (Chebil et al, 2014). Symptoms included the decline or death of plant parts and, eventually, of whole vines due to a variety of necrosis phenomena, such as cankers, browning, vascular streaking, longitudinal lesions, and cane bleaching, which affect the woody parts of the plant (Luque et al, 2009).…”
mentioning
confidence: 99%
“…In fact, Botryosphaeriaceae species were recorded for the first time by Linaldeddu et al (2008) on P. pinaster and P. radiata , then by Chattaoui et al (2012) on Olea europea and again by Linaldeddu et al (2013) on Quercus suber . Botryosphaeria‐related dieback was reported also on grapevine (Chebil et al, 2014), on Almond trees (Gharbi et al, 2017) and recently on Q. coccifera (Hlaiem et al, 2020). According to our survey in Northern Tunisia (Bizerte, Rimel forest), disease symptoms on P. halepensis trees include shoot dieback, wood necrosis, branch cankers, crown wilt, vascular discoloration in wood, innumerable pycnidia on infected tissues, stem blight with poor growth and sudden death of the whole tree are similar to those observed on Eucalyptus trees in Australia and South Africa (Slippers et al, 2004), on kermes oak in Greece (Tsopelas et al, 2010) and on grapevine in California (Urbez‐Torres, 2011; Urbez‐Torres, Leavitt, Voegel, & Gubler, 2006).…”
Section: Discussionmentioning
confidence: 88%
“…Botryosphaeria-related dieback was reported also on grapevine (Chebil et al, 2014), on Almond trees (Gharbi et al, 2017) and recently on Q. coccifera (Hlaiem et al, 2020). According to our survey in Northern Tunisia (Bizerte, Rimel forest), disease symptoms on P. halepensis trees include shoot dieback, wood necrosis, branch cankers, crown wilt, vascular discoloration in wood, innumerable pycnidia on infected tissues, stem blight with poor growth and sudden death of the whole tree are similar to those observed on Eucalyptus trees in Australia and South Africa (Slippers et al, 2004), on kermes oak in Greece (Tsopelas et al, 2010) and Linaldeddu et al, 2016).…”
Section: Discussionmentioning
confidence: 89%